If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20f + -5f + 6 = 9f + -10 Reorder the terms: 6 + 20f + -5f = 9f + -10 Combine like terms: 20f + -5f = 15f 6 + 15f = 9f + -10 Reorder the terms: 6 + 15f = -10 + 9f Solving 6 + 15f = -10 + 9f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-9f' to each side of the equation. 6 + 15f + -9f = -10 + 9f + -9f Combine like terms: 15f + -9f = 6f 6 + 6f = -10 + 9f + -9f Combine like terms: 9f + -9f = 0 6 + 6f = -10 + 0 6 + 6f = -10 Add '-6' to each side of the equation. 6 + -6 + 6f = -10 + -6 Combine like terms: 6 + -6 = 0 0 + 6f = -10 + -6 6f = -10 + -6 Combine like terms: -10 + -6 = -16 6f = -16 Divide each side by '6'. f = -2.666666667 Simplifying f = -2.666666667
| 4x+-25+115=180 | | -2x-4=3x+3 | | 14(3x+-5)=56 | | 24n+20=3n | | 6(-5x-1)=84 | | 18(-7x-3)+4= | | 6x-12=4x+68 | | 4n-12=3-2n | | 14-12(13-19p)= | | 3x+15=3x(x+5) | | 10a-3m=22 | | 9n-3n=2n+8 | | 10+9(6q+4)= | | 2-(2.27)= | | 3n+15=n-15 | | 22-5(6v-1)=-7 | | -18p+13+15-3p= | | 81+x-6=5 | | 5(-2n-4)=-80 | | -3p^3+p^2+3p+1=0 | | 2-2.27= | | -2=.25x+2 | | -2.5x^2-7.1x+2.2=3.7 | | [3/4a-3]=9 | | 8(-19+15y)= | | 5x+123=3x+90 | | -17(2s+10)-9s= | | 3n+9=-18 | | [-2y+6]=6 | | 2(6+3n)-4= | | 3q=7 | | 2x+3+2=5x-3 |